Self-adaptive algorithms for the split problem of the demicontractive operators - Yao, Yonghong; Liou, Yeong-Cheng; Postolache, Mihai (Optimization, 2018)
Self-adaptive algorithms are presented for solving the split common fixed point problem of demicontractive operators in Hilbert spaces. Weak and strong convergence theorems are given under some mild assumptions.